Highly Selective Photoreduction of CO2 with Suppressing H2 Evolution by Plasmonic Au/CdSe–Cu2O Hierarchical Nanostructures under Visible Light. Issue 18 (9th April 2020) - Wang, Hongzhi; Rong, Hongpan; Wang, Dong; Li, Xinyuan; Zhang, Erhuan; Wan, Xiaodong; Bai, Bing; Xu, Meng; Liu, Jiajia; Liu, Jia; Chen, Wenxing; Zhang, Jiatao
Abstract: Here, the photocatalytic CO2 reduction reaction (CO2 RR) with the selectivity of carbon products up to 100% is realized by completely suppressing the H2 evolution reaction under visible light (λ > 420 nm) irradiation. To target this, plasmonic Au/CdSe dumbbell nanorods enhance light harvesting and produce a plasmon‐enhanced charge‐rich environment; peripheral Cu2 O provides rich active sites for CO2 reduction and suppresses the hydrogen generation to improve the selectivity of carbon products. The middle CdSe serves as a bridge to transfer the photocharges. Based on synthesizing these Au/CdSe–Cu2 O hierarchical nanostructures (HNSs), efficient photoinduced electron/hole (e − /h + ) separation and 100% of CO selectivity can be realized. Also, the 2e − /2H + products of CO can be further enhanced and hydrogenated to effectively complete 8e − /8H + reduction of CO2 to methane (CH4 ), where a sufficient CO concentration and the proton provided by H2 O reduction are indispensable. Under the optimum condition, the Au/CdSe–Cu2 O HNSs display high photocatalytic activity and stability, where the stable gas generation rates are 254 and 123 µmol g −1 h −1 for CO and CH4 over a 60 h period. Abstract : The photocatalytic CO2 reduction reaction (CO2 RR) with the selectivity of carbon products up to 100% is realized under visible light irradiation. Under the optimal catalytic condition, the Au/CdSe–Cu2 O hierarchical nanostructures (HNSs) display high photocatalytic activity and stability, where the stable gas generation rates are 254 and 123 μmol g −1 h −1 for CO and CH4 over a 60 h period, respectively.